2017
DOI: 10.1016/j.neuropsychologia.2017.01.005
|View full text |Cite
|
Sign up to set email alerts
|

Dissociation between working memory performance and proactive interference control in post-traumatic stress disorder

Abstract: Deficits in working memory (WM) and cognitive control processes have been reported in post-traumatic stress disorder (PTSD), in addition to clinical symptoms such as hypervigilance, re-experiencing, and avoidance of trauma reminders. Given the uncontrollable nature of intrusive memories, an important question is whether PTSD is associated with altered control of interference in WM. Some studies also suggest that episodic memory shows a material-specific dissociation in PTSD, with greater impairments in verbal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
35
2
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(42 citation statements)
references
References 106 publications
4
35
2
1
Order By: Relevance
“…As noted previously, deficits in executive control contribute to the development and maintenance of PTSD (LoSavio, Dillon, & Resick, 2017;Swick, Cayton, Ashley, & Turken, 2017). Recent findings also demonstrate that worse executive control predicts increased inflammatory reactivity to emotional distress (Shields, Kuchenbecker, Pressman, Sumida, & Slavich, 2016).…”
Section: Nontrauma-focused Behavioral Interventions For Ptsdsupporting
confidence: 53%
“…As noted previously, deficits in executive control contribute to the development and maintenance of PTSD (LoSavio, Dillon, & Resick, 2017;Swick, Cayton, Ashley, & Turken, 2017). Recent findings also demonstrate that worse executive control predicts increased inflammatory reactivity to emotional distress (Shields, Kuchenbecker, Pressman, Sumida, & Slavich, 2016).…”
Section: Nontrauma-focused Behavioral Interventions For Ptsdsupporting
confidence: 53%
“…In general, PTSD is accompanied by depression, anxiety, and alcohol-use disorders; it causes not only physical and mental disorders, but also social and occupational problems [ 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 ]. It is characterized by cognitive dysfunction, and it may lead to problems of observation and control of information, which interferes with work performance and leads to the limitations of work demands [ 15 , 16 , 17 , 18 ]. In addition, it causes symptoms such as fatigue, loss of concentration, loss of interest in activities, sleep disorders, social atrophy, vigilance, and behavioral avoidance, increasing absenteeism and causing problems in efficiency and social relations in the workplace [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, neurobiological research has failed to support this model, showing that high fantasy prone healthy controls instructed and motivated to simulate DID were not able to enact brain activation patterns and physiological activation of individuals with DID (Reinders, Willemsen, Vos, den Boer, & Nijenhuis, 2012;Schlumpf et al, 2013Schlumpf et al, , 2014. Research on cognitive functioning, dissociative symptoms and DID has produced conflicting results: some studies (Dorahy, 2001) on memory and dissociative disorders showed potential deficits in working memory of DID individuals, while several other studies documented that dissociation was linked to better task-performance in working memory tasks accompanied by increased brain activation (Elzinga et al, 2007;Swick, Cayton, Ashley, & Turken, 2017;Veltman et al, 2005). Consequently, research requires further replication and validation.…”
Section: Introductionmentioning
confidence: 99%